Case Report: Replacement of PD-1 inhibitors with PD-L1 inhibitors in the treatment of squamous non-small-cell lung carcinoma - Wu, Tong; Li, Yujun; Cui, Xiaonan; Zhang, Chunxia (Frontiers in Immunology, 2023)
Background: Immune checkpoint inhibitor (ICIs)-associated cardiotoxicity is a relatively uncommon immune-related adverse effects (irAEs) with a high mortality rate. There are few recommendations for the replacement of different immune checkpoint inhibitor in domestic and international reports.Case presentation: We report a case of a patient with squamous non-small cell lung carcinoma (squamous NSCLC) who developed cardiotoxicity after being treated with programmed death-1 (PD-1) inhibitor and then changed to PD-L1 inhibitor to continue the treatment. A significant benefit was observed after 4 cycles of immunotherapy, and no further cardiotoxicity occurred after the treatment was started.This case demonstrates that myocardial damage induced by Tislelizumab (PD-1 inhibitor) can be improved after switching to Sugemalimab (PD-L1 inhibitor) and that antitumor immunotherapy is effective. This result may have important implications for optimizing immunotherapy management regimens in cancer patients.